2020
DOI: 10.1002/cbdv.202000296
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Flavonoids and Other Compounds from the Aerial Parts of Vernonia guineensis Benth. (Asteraceae)

Abstract: An extensive phytochemical study of the aerial parts of Vernonia guineensis Benth. (Asteraceae) led to the isolation of a new flavone, vernoguinoflavone and a naturally isolated glycerol ester, eicosanoic acid 2‐hydroxy‐1,3‐propanediyl ester, together with eighteen known secondary metabolites including quercetin, luteolin, vernopicrin, vernomelitensin, β‐amyrin, oleanolic acid, ursolic acid, lupeol, betulinic acid, β‐carotene, a mixture of stigmasterol and β‐sitosterol, β‐sitosterol‐3‐O‐β‐D‐glucoside, 2,3‐dihy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Reported MIC values of LUT against E. coli and Salmonella strains vary in the literature. Wouamba et al [57] reported a low MIC of 3.12 µg/mL against E. coli and 6.25 µg/mL against S. Typhimurium; however, only one reference strain per each bacterial species was tested in their study. MIC values of 64 µg/mL were obtained by Qian et al [58] when they tested the activity of LUT against four strains of E. coli, including one ATCC strain and three isolates from raw pork meat.…”
Section: Discussionmentioning
confidence: 93%
“…Reported MIC values of LUT against E. coli and Salmonella strains vary in the literature. Wouamba et al [57] reported a low MIC of 3.12 µg/mL against E. coli and 6.25 µg/mL against S. Typhimurium; however, only one reference strain per each bacterial species was tested in their study. MIC values of 64 µg/mL were obtained by Qian et al [58] when they tested the activity of LUT against four strains of E. coli, including one ATCC strain and three isolates from raw pork meat.…”
Section: Discussionmentioning
confidence: 93%
“…The antiplasmodial bioassay-guided investigation of H. lanceolatum twigs and stem bark methanolic extract led to the identification of the dichloromethane-soluble fraction as the most active one from which four distinct compounds ( Figure 3 ) have been isolated as major leads with significant yields in the range of 0.05–0.15% of the dichloromethane active subextract ( Table 1 ). The structure elucidation of the isolated compounds was conducted by exploration of their spectral data (see Figures S 1 –S 8 on supplementary data) which allow their characterization as two xanthones including 1,6-dihydroxyxanthone ( 1 ) [ 31 ] and norathyriol ( 2 ) [ 32 ] as well as two triterpenes, namely, betulinic acid ( 3 ) [ 14 , 33 ] and ursolic acid ( 4 ) [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The identification of the constituents of the hydroethanolic extract prepared from the leaf powder of M. inermis was carried out by a rapid untargeted UHPLC-QTOF-ESIMS/MS-Based metabolomic profiling method described by Wouamba et al [ 19 ] and the main results obtained are recorded in Table 1 . Fifteen compounds were identified ( Fig.…”
Section: Resultsmentioning
confidence: 99%